Tujuan dan Fungsi Filsafat Pendidikan Islam dalam Pengembangan Pembelajaran Siswa - Mardiah, Aida; Jannah, Nur; S, Sakdiani; Bintang, Tri Kumala; Harahap, Wahit Gunadi (Madani: Jurnal Ilmiah Multidisiplin, 2024)
The goal of general education is to realize the positive changes that students expect after the end of the educational process, in the form of changes in individual behavior, personal life, as well as social life and the natural environment. Students live their lives. The goal of education is the core issue of education and the core of all pedagogical considerations. Education Islam is a universal aspect of Islam. The aim of Islamic education for students is to know the true nature of the Islamic religion, so that students can study, understand and practice the teachings of the Islamic religion. So that the direction of life of students is guided and guided and correct. The philosophy of Islamic education is a concept of thinking about education that is based on the teachings of the Islamic religion regarding the nature of human abilities so that they can be nurtured, developed and guided to become Muslim humans whose entire personality is imbued with Islamic teachings. As a general theory regarding the education system, Islamic educational philosophy functions as the foundation for the framework of an educational system that will function in applying the teachings of the Islamic religion in the field of education, whose goals are identical to the goals to be achieved by Islamic teachings themselves. This research aims to find out how big the goals and functions of Islamic educational philosophy are in developing student learning. What are the benefits for students of Islamic education and its positive influence on student learning. This research uses a literature analysis study method by analyzing or reading several writings or scientific works in the form of books from journals and other articles. So that the author can complete this journal article.